Overcoming Difficulties in Building Therapeutic Relationships in Counseling - Bunga Afasli; Yeni Karneli; Mudjiran (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The therapeutic relationship is at the core of effective counseling, where a strong alliance between counselor and client builds trust and supports positive change. This process involves empathy, mutual understanding and openness. However, building an effective relationship is often faced with various barriers, both on the part of the counselor and the client, such as communication gaps, resistance, or differences in values. Contextual barriers, such as cultural differences or limited facilities, can also affect the quality of this relationship. Counselors should be able to overcome such barriers with a flexible approach, improve interpersonal skills, and demonstrate empathy and active listening. In addition, it is important to build clients' trust by creating an environment that is safe and sensitive to their cultural background. The purpose of this article is to discuss the barriers in the therapeutic relationship and strategies to overcome them, with the aim of increasing the effectiveness of the counseling process and providing greater positive impact for clients. The research method in this article uses a literature study which is to obtain references that are in accordance with the direction and purpose of this article. Through this article, it is expected to be able to know and expand the reading on how to build therapeutic relationships in counseling.